1, 2‐(Bis)trifluoromethylation of Alkynes: A One‐Step Reaction to Install an Underutilized Functional Group. Issue 34 (11th July 2019) - Guo, Shuo; AbuSalim, Deyaa I.; Cook, Silas P.
Abstract: Modifying the electronic properties of olefins is the quintessential approach to tuning alkene reactivity. In this context, the exploration of trifluoromethyl groups as divergent electronic modifiers has not been considered. In this work, we describe a copper‐mediated 1, 2‐(bis)trifluoromethylation of acetylenes to create E ‐hexafluorobutenes ( E ‐HFBs) under blue light in a single step. The reaction proceeds with high yield and E / Z selectivity. Since the alkyne captures two trifluoromethyl groups from each molecule of bpyCu(CF3 )3, mechanistic studies were conducted to illuminate the role of the reactants. Interestingly, E ‐HFBs exhibit remarkable stability to standard olefin functionalization reactions in spite of the pendant trifluoromethyl groups. This finding has significant implications for medicine, agroscience, and materials. Abstract : Two of a kind : A copper‐mediated 1, 2‐(bis)trifluoromethylation of acetylenes enables the preparation of E ‐hexafluorobutenes ( E ‐HFBs) in a single step. The reaction proceeds with high yield and E / Z selectivity under blue light. Mechanistic work elucidates the frontier molecular orbital behavior of the copper complex and the role of persulfate.